Some species of Valeriana L.: comparative description of fruit morphology - M. М. Ishmuratova; A. R. Ishbirdin; E. N. Suleymanova; N. I. Baryshnikova (Proceedings on applied botany, genetics and breeding, 2024)
A case study of 33 cenopopulations (South Urals, and Central Yakutia) and 8 herbarium specimens of Valeriana L. was used to make a comparative analysis of qualitative (fruit shape, color, and pubescence) and quantitative (fruit length, width, and length-to-width ratio) morphological characters, and 1000 fruit weight among the species Valeriana officinalis L., V. alternifolia Ledeb., V. dubia Bunge, V. wolgensis Kazak. and V. tuberosa L. Fruits of V. officinalis were found to be relatively light and small, those of V. alternifolia and V. tuberosa were relatively heavy, and those of V. wolgensis were large. Fruit indices (length-to-width ratios) of V. officinalis and V. wolgensis were higher than 2, while those of the remaining species were about 2. Dependence of fruit size characteristics on altitudes, latitudes, and weather conditions was shown. Intrapopulation variability of morphological features in fruits was, as a rule, low or very low. Fruit length variability was lower in most species than the variability of their fruit widths or fruit indices. The contribution of interspecific variability to the variation in the quantitative traits of fruits exceeded the contribution of interpopulation variability. Qualitative and quantitative fruit characters of Valeriana L. spp. can be used as additional taxonomic indicators for their differentiation. The keys are provided for identification of species according to their fruit characters.